2007
DOI: 10.1677/joe-07-0128
|View full text |Cite
|
Sign up to set email alerts
|

PTGER1 and PTGER2 receptors mediate regulation of progesterone synthesis and type 1 11β-hydroxysteroid dehydrogenase activity by prostaglandin E2 in human granulosa–lutein cells

Abstract: In luteinizing granulosa cells, prostaglandin E2 (PGE2) can exert luteotrophic actions, apparently via the cAMP signalling pathway. In addition to stimulating progesterone synthesis, PGE2 can also stimulate oxidation of the physiological glucocorticoid, cortisol, to its inactive metabolite, cortisone, by the type 1 11β-hydroxysteroid dehydrogenase (11βHSD1) enzyme in human granulosa–lutein cells. Having previously shown these human ovarian cells to express functional G-protein coupled, E-series prostaglandin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…It had been assumed that this was true of all tissues, but recent studies have established that the predominant direction of activity for HSD11B1 is sensitive to the ratio of NADPH/NADP C in the lumen of the smooth endoplasmic reticulum, which in turn depends on carbohydrate metabolism by hexose-6-phosphate dehydrogenase (Draper et al 2003, Atanasov et al 2004, Banhegyi et al 2004, Bujalska et al 2005, Czegle et al 2006, McCormick et al 2006, Odermatt et al 2006, White et al 2007). While it is conventionally accepted that pyruvate and glutamine (and to a lesser extent acetyl-CoA derived from non-esterified fatty acids) are the major respiratory substrates for mammalian oocytes (Downs et al 1997, Downs & Hudson 2000, Johnson et al 2007, Songsasen et al 2007, there are emerging roles for glycolytic oxidation of glucose and the pentose phosphate pathway in oocyte maturation (Downs et al 1998, Harris et al 2007). This could set the balance of NADPH/NADP C in the mammalian oocyte such that HSD11B1 acts as a predominant 11b-dehydrogenase enzyme to inactivate glucocorticoids.…”
Section: Nadp(h)-dependent Activities Of Hsd11b1 Without Affecting Thmentioning
confidence: 99%
See 1 more Smart Citation
“…It had been assumed that this was true of all tissues, but recent studies have established that the predominant direction of activity for HSD11B1 is sensitive to the ratio of NADPH/NADP C in the lumen of the smooth endoplasmic reticulum, which in turn depends on carbohydrate metabolism by hexose-6-phosphate dehydrogenase (Draper et al 2003, Atanasov et al 2004, Banhegyi et al 2004, Bujalska et al 2005, Czegle et al 2006, McCormick et al 2006, Odermatt et al 2006, White et al 2007). While it is conventionally accepted that pyruvate and glutamine (and to a lesser extent acetyl-CoA derived from non-esterified fatty acids) are the major respiratory substrates for mammalian oocytes (Downs et al 1997, Downs & Hudson 2000, Johnson et al 2007, Songsasen et al 2007, there are emerging roles for glycolytic oxidation of glucose and the pentose phosphate pathway in oocyte maturation (Downs et al 1998, Harris et al 2007). This could set the balance of NADPH/NADP C in the mammalian oocyte such that HSD11B1 acts as a predominant 11b-dehydrogenase enzyme to inactivate glucocorticoids.…”
Section: Nadp(h)-dependent Activities Of Hsd11b1 Without Affecting Thmentioning
confidence: 99%
“…In the mammalian ovary, the expression and activity of HSD11B1 are sensitive to a variety of endocrine/ pararcine regulators, including LH/hCG (Tetsuka et al 1997, Thurston et al 2003c and prostaglandin E 2 (Jonas et al 2006, Chandras et al 2007. In expanded COCs, it seems likely that the enclosed oocytes would have been subjected to the start of an LH surge in vivo prior to isolation which could account for their relatively high levels of cortisol oxidation.…”
Section: Nadp(h)-dependent Activities Of Hsd11b1 Without Affecting Thmentioning
confidence: 99%
“…This suggests that MR in granulosa cells may be activated by aldosterone. In contrast, bovine and human granulosa cells were found to express 11b-HSD1, but not 11b-HSD2 (Tetsuka et al 2003;Chandras et al 2007). Other studies showed that human granulosa cells expressed 11b-HSD2 message during the follicular phase, and upon stimulation, ceased to express 11b-HSD2 and began to express 11b-HSD1 (Thurston et al 2003a).…”
Section: Discussionmentioning
confidence: 84%
“…Chandras et al [51] implicated PTGER2 receptors as mediators of the stimulation of progesterone synthesis in a human ovarian cell model in vitro. It was suggested also that PTGER1 receptors participate in the stimulation of steroidogenesis by PGE2 but do not mediate the full steroidogenic response.…”
Section: Discussionmentioning
confidence: 99%